if
![a = \frac{2 - \sqrt{3} }{2} a = \frac{2 - \sqrt{3} }{2}](https://tex.z-dn.net/?f=a+%3D++%5Cfrac%7B2+-++%5Csqrt%7B3%7D+%7D%7B2%7D+)
then find the value of
![{a}^{2} + \frac{1}{ {a}^{2} } {a}^{2} + \frac{1}{ {a}^{2} }](https://tex.z-dn.net/?f=+%7Ba%7D%5E%7B2%7D++%2B++%5Cfrac%7B1%7D%7B+%7Ba%7D%5E%7B2%7D+%7D+)
Answers
Answered by
1
Step-by-step explanation:
a=(2-√3)/2
a^2=(2-√3)^2/4
=(4+3-4√3)/4
=(7-4√3)/4
1/a^2=4/(7-4√3)
=4(7+4√3)/(7-4√3)(7+4√3)
=4(7+4√3)/(7^2-4√3^2)
=4(7+4√3)/(49-48)
=4(7+4√3)
so,
a^2+1/a^2
=(7-4√3)/4+4(7+4√3)
={(7-4√3)+16(7+4√3)}/4
=(7-4√3+112+64√3)/4
=(119+60√3)/4
=119/4+15√3
Similar questions